Second-language learning and changes in the brain - Osterhout, Lee; Poliakov, Andrew; Inoue, Kayo; McLaughlin, Judith; Valentine, Geoffrey; Pitkanen, Ilona; Frenck-Mestre, Cheryl; Hirschensohn, Julia (Journal of neurolinguistics, 2008)
Presumably, second-language (L2) learning is mediated by changes in the brain. Little is known about what changes in the brain, how the brain changes, or when these changes occur during learning. Here, we illustrate by way of example how modern brain-based methods can be used to discern some of the changes that occur during L2 learning. Preliminary results from three studies indicate that classroom-based L2 instruction can result in changes in the brain's electrical activity, in the location of this activity within the brain, and in the structure of the learners’ brains. These changes can occur during the earliest stages of L2 acquisition.